Recent Results on Belief, Knowledge and the Epistemic Foundations of Game Theory - Giacomo Bonanno; Pierpaolo Battigalli (University of California, Department of Economics, 1998)
We provide a self-contained, selective overview of the literature on the role of knowledge and beliefs in game theory. We focus on recent results on the epistemic foundations of solution concepts, including correlated equilibrium, rationalizability in dynamic games, forward and backward induction.
Keywords: 330